Prototipe Solar Tracking Berbasis Arduino dan Sensor Light Dependent Resistor (LDR) - Bangun Aji Saputra; Alfian Ma'arif (Buletin Ilmiah Sarjana Teknik Elektro, 2022)
The government prioritizes the availability of electrical energy, especially in the industrial sector and urban areas, but the infrastructure to provide access to electricity in rural areas, especially street lighting, is still very lacking as a result of the need for a different energy source to overcome this problem. Solar cells are power plants that can convert solar energy into electricity, but most solar panels are installed statically which results in less than optimal absorption of solar energy. The purpose of this research is to make a prototype solar tracking based on the Arduino Mega 2560 microcontroller with the fuzzy logic method with an LDR sensor as a light sensor and a servo motor as a driver so that the solar panel can track the movement of the sun to get the maximum light intensity. The results of this study there are four test conditions which indicate that the percentage of the comparison value of solar panels statically and tracking in cloudy conditions is 34.07% while the test in cloudy sunny conditions is 25.603%. Pemerintah memprioritaskan ketersediaan energi listrik khususnya di sektor industri dan wilayah perkotaan tetapi infrastruktur untuk memberikan akses listrik di daerah pedesaan terutama penerangan jalan masih sangatlah kurang akibatnya perlunya sumber energi yang berbeda diperlukan untuk mengatasi masalah ini. Sel surya adalah pembangkit listrik yang dapat mengubah energi matahari menjadi listrik namun sebagian besar Panel surya dipasang secara statis yang mengakibatkan penyerapan energi matahari kurang optimal. Tujuan dari penelitian ini adalah membuat Prototype solar tracking berbasis mikrokontroler Arduino Mega 2560 dengan metode fuzzy logic dengan sensor LDR sebagai sensor cahaya dan motor servo sebagai penggerak sehingga panel surya dapat melacak pergerakan matahari untuk mendapatkan intensitas cahaya yang maksimal. Hasil dari penelitian ini terdapat empat kondisi pengujian yang menunjukkan bahwa persentase nilai perbandingan panel surya secara statis dan tracking dalam kondisi mendung sebesar 34,07% sedangkan pengujian dalam kondisi cerah Berawan sebesar 25,603%.